ENCOUNTER OF ISLAMIC IDEOLOGY RADICALISM ABOUT HOMOSEXUAL DISCOURSE IN REPUBLIKA AND TEMPO NEWSPAPER - Fita Fathurokhmah (Jurnal Penelitian dan Pengembangan Komunikasi dan Informatika, 2015)
The clash of Islamis of media ideologies related to Islamic radicalism in covering homosexual as the society major problem. How does media constructs texts in discoursing homosexual, what factors do influence, how socio-cultural factors influence the discourse, discoursing process of such reality. In the level of text analysis, occupies framing analysis from Robert Ethmen. Text production, consumption, socio-cultural, uses Ideology of media theory Louis Althuser. Multilevel analysis used is critical discourse analysis Norman Fairclough. Qualitative approach with a critical paradigm that describes the observed reality behind reality that does not appear in the newspapers. Conclusions: There are differences Republika and Koran Tempo presenting a discoursing of homosexual. Republika newspaper has practice dominated and power with ideology of Islamic radicalism by preaching that refers to the Islamic fatwa, news of FPI violence as a form of disagreement with the understanding homosexual, porn movies circulation. The newspaper stated that homosexuality was banned religion and need to be confronted in order not to spread in the community. Homosexuals as a despicable act, distorted, need therapy, medical healing. Koran Tempo was directing the reader to the radicalism of thought in Islam that the Homosexual rights of every individual who needs to be respected while forbidden in Islam. Koran Tempo steers and influences the reader so that people pick the renewal of thought with respect homosexuals as quoted in the news of the JIL. The media ideology of Islamic radicalism about homosexuals affects the production and consumption process. Staff production and journalists adhering to different ideologies both of these media. Socio-cultural practices affect the homosexual discourse. President Susilo Bambang Yudhoyono is implement democratization, respect for differences of opinion, then Homosexual controversy in Indonesia, he acted accommodate all public opinion and ultimately reports in the media, SBY is not too intervene as President he only called on the media to cover both side of doing. Key words: Media ideology, Discourse, Islamic Radicalism, Homosexual